Second-step lectotypification of Fimbristylis alboviridis (Cyperaceae) - Kumar, Anand; Bharati, Kumar Avinash (Phytotaxa, 2020)
Fimbristylis alboviridis C.B. Clarke (1893: 638) was described based on the collections of Griffith, Hooker and Jenkins from East Bengal, River Megna and Upper Assam, respectively. The species is mainly distributed in West & West Central tropical Africa, tropical Asia, Indo-China and Malesia (Govaerts et al. 2020). In India, it is confined to Andhra Pradesh, Assam, Bihar, Goa, Karnataka, Madhya Pradesh, Maharashtra, Meghalaya and Uttar Pradesh (Patil & Prasad 2009, Anitha 2011, Prasad 2017, Kumar et al. 2017). The species is often confused with F. dichotoma (Linnaeus 1753: 50) Vahl (1805: 287). Fimbristylis alboviridis is characterized by nutlets bearing 10 to 16 vertical rows on either side while the latter has 5 to 10 rows (Prasad 2017).